Steinmann pin retractor-assisted reduction with circle plate fixation via sinus tarsi approach for intra-articular calcaneal fractures: a retrospective cohort study - Bin Zhao; Wenqian Zhao; Isaac Assan (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Sinus tarsi approach and mini-calc plate have been used for intra-articular calcaneal fractures. However, the sinus tarsi approach has limited exposure to the lateral wall, which makes it challenging to obtain an excellent anatomic reduction of the calcaneal body. What is more! To restore the width of the calcaneal body entirely and prevent the heel varus simultaneously with mini-calc plate was tough as well. Aimed to solve the aforementioned problems, our study focused on using the Steinmann pin retractor for reduction and the circle plate for fixation via the sinus tarsi approach. Methods From March 2017 to January 2019, 15 patients with closed calcaneal fractures were treated with the method of Steinmann pin retractor-assisted reduction and circle plate fixation via the sinus tarsi approach. All these patients received a positive postoperative clinical and radiological evaluation. Results A postoperative follow-up was done for each of the 15 patients, and the following scores and parameters were observed: value of visual analogue scale (VAS) was 1.44 ± 0.63, and The American Orthopaedic Foot and Ankle Score (AOFAS) Ankle-Hindfoot score was 84.31 ± 5.03 at the last follow-up. The Böhler angle (30.81 ± 3.56°), width (37.83 ± 4.87 mm), length (87.4 ± 3.33 mm), and height (86.23 ± 5.36 mm) of the calcaneus were improved significantly in comparison with preoperative values (− 0.94 ± 10.06°, 45.67 ± 5.68 mm, 82.72 ± 5.54 mm, 76.32 ± 7.98 mm), and these parameters were maintained excellently after 6–19 months’ follow-up. Conclusion Our present study suggested that Steinmann pin retractor-assisted reduction with circle plate fixation via the sinus tarsi approach may serve as a safe and effective method for Sanders type II and type III calcaneus fractures. The Böhler angle, height, length, and body of the calcaneus were excellently restored postoperatively and maintained at last follow-up and rare postoperative complications. Trial registration This study has been registered. The unique identifying number is research registry 5092.